ANALISIS PENGARUH KONSTRUKSI PADA PENINGKATAN PDRB KOTA BATAM - Elvina Enjelica; Felix Filbert; Jeny; Trillian Lim (Journal of Innovation Research and Knowledge, 2021)
The economic development of each region can be seen from the increase in the regional GRDP. Currently, Batam City has achieved a fairly good economic growth, which is assisted by construction factors. This development was investigated by the authors using qualitative research methods and the researchers also analyzed the effect of construction on PDRB growth. From the research that has been conducted, it shows that the results obtained are explaining the growth of PDRB in 2015-2020 which has experienced a significant increase and PDRB of Batam City has decreased in 2020 due to the spread of Covid-19. In 2020 there was a decline in PDRB in batam, which was the impact of Covid-19 which required a temporary stop of development.